2016
DOI: 10.4102/sajhrm.v14i1.728
|View full text |Cite
|
Sign up to set email alerts
|

Employees' perceptions of the effectiveness and fairness of performance management in a South African public sector institution

Abstract: Orientation: The implementation of performance management systems (PMSs) and performance appraisals (PAs) by public managers remains a challenge and necessitates an investigation into employees’ perceptions of the effectiveness of the PMS and the fairness of PA.Research purpose: This study investigated the association between employee involvement, performance-oriented culture, management commitment and the effectiveness of a PMS. Six factors that determine and influence employees’ perceptions of PA fairness we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Cook e Crossman (2004) alertam que é necessário considerar as opiniões dos envolvidos para que esse Sistema seja validado e reconhecido como justo. Como exemplo, cita-se que, devido à falta de participação dos funcionários no processo de Avaliação de Desempenho e na definição de metas, bem como a falta de sessões regulares de feedback de desempenho, o Sistema de Avaliação de uma organização pública da África do Sul foi considerado ineficaz e injusto pelos funcionários (MAKHUBELA, BOTHA, SWANEPOEL, 2016).…”
Section: Análise Bibliométrica: Características Avançadasunclassified
“…Cook e Crossman (2004) alertam que é necessário considerar as opiniões dos envolvidos para que esse Sistema seja validado e reconhecido como justo. Como exemplo, cita-se que, devido à falta de participação dos funcionários no processo de Avaliação de Desempenho e na definição de metas, bem como a falta de sessões regulares de feedback de desempenho, o Sistema de Avaliação de uma organização pública da África do Sul foi considerado ineficaz e injusto pelos funcionários (MAKHUBELA, BOTHA, SWANEPOEL, 2016).…”
Section: Análise Bibliométrica: Características Avançadasunclassified
“…This kind of survey was used to answer what, when, where and how questions (Babbie, 2010). A quantitative survey design was followed by various other studies measuring the perceptions of employees regarding the effectiveness of the PMS (Dewettinck & Van Dijk, 2013;Haines & St-Onge, 2012;Makhubela et al, 2016;Ramulumisi et al, 2015;Sharma et al, 2016).…”
Section: Research Approachmentioning
confidence: 99%
“…Haines and St-Onge (2012) researched PMS effectiveness in both public and private organisations in Canada. In the South African context, Ramulumisi, Schultz and Jordaan (2015) measured the effectiveness of the PMS in a government department, while Makhubela, Botha and Swanepoel (2016) did a similar study in a public sector institution. The limitations of these studies were that the scales developed to measure the effectiveness of the PMS did not extensively cover all the phases of the PMS.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion will be include certain things like coating, mentoring feedback and assessment. Makhubela et. al., (2016) reported that implementation of the performance management system will help to provide adequate knowledge about the performance levels of the employees in the organization.…”
Section: Introductionmentioning
confidence: 99%